A Viologen Polymer and a Compact Ferrocene: Comparison of Solution Viscosities and Their Performance in a Redox Flow Battery with a Size Exclusion Membrane. Issue 2 (19th December 2021) - Borchers, Philipp S.; Elbert, Johannes; Anufriev, Ilya; Strumpf, Maria; Nischang, Ivo; Hager, Martin D.; Schubert, Ulrich S.
Abstract: In this work, the synthesis and characterization of a compact, ferrocene tetramer and a linear viologen polymer is reported. The latter material is a new, 4, 4′‐bipyridine containing, organo‐soluble polymer. As aimed for solubility in nonpolar solvents, a 2‐ethylhexyl‐moiety to promote organosolubility and 4‐vinylbenzyl serving as a polymerizable group are introduced to a 4, 4′‐bipyridine. The halide anions of the monomer cation are exchanged to bis(trifluoromethansulfon)imide, which further enhances organosolubility. The monomer is subsequently copolymerized with styrene by free radical polymerization. In addition, a four‐ferrocene‐containing compact structure, based on pentaerythritol, is synthesized via the straightforward radical thiol‐ene reaction. The polymer solutions are thoroughly characterized hydrodynamically. Subsequently, propylene carbonate‐based solutions of both materials are prepared to allow an assessment for future energy storage applications. This is done by testing battery characteristics in a custom‐made flow‐cell with a simple dialysis membrane for physical separation of the active materials. The capability of energy storage is verified by leaving the charged materials in solution in an open circuit for 24 h. Here, more than 99% of the stored charges can be recovered. Cycling the battery for 100 times reveals the remarkable stability of the materials of only 0.2% capacity loss per day in the battery setup. Abstract : A new, 4, 4′‐bipyridine containing, organosoluble monomer is synthesized, its use as a precursor for polymers is investigated, and its solution characteristics studied. A multiple ferrocene moiety‐containing molecularly more compact material is synthesized, enabling a battery with high capacity retention over multiple days of cycling. Solution properties are accessed to study the materials, that is, linear polymers and more compact structures.